It is time to bridge the gap between exploring and exploiting: prospects for utilizing intraspecific genetic variation to optimize arthropods for augmentative pest control – a review. Issue 2 (26th November 2016) - Lommen, Suzanne T.E.; de Jong, Peter W.; Pannebakker, Bart A.
Abstract: Intraspecific genetic variation in arthropods is often studied in the context of evolution and ecology. Such knowledge, however, can also be very usefully applied to biological pest control. Selection of genotypes with optimal trait values may be a powerful tool to develop more effective biocontrol agents. Although it has repeatedly been proposed, this approach is still hardly applied in the current commercial development of arthropod agents for pest control. In this perspective study, we call to take advantage of the increasing knowledge on the genetics underlying intraspecific variation to improve biological control agents. We argue that it is timely now because at present both the need and the technical possibilities for implementation exist, as there is (1) increased economic importance of biocontrol, (2) reduced availability of exotic biocontrol agents due to stricter legislation, and (3) increased availability of genetic information on non‐model species. We present a step‐by‐step approach towards the exploitation of intraspecific genetic variation for biocontrol, outline that knowledge of the underlying genetic mechanisms is essential for success, and indicate how new molecular techniques can facilitate this. Finally, we exemplify this procedure by two case studies, one focussing on a target trait – offspring sex ratio – across species of hymenopteran parasitoids, and the other on a target species – the two‐spot ladybird beetle – where wing length and body colouration can be optimized for aphid control. With this overview, we aim to inspire scientific researchers and biocontrol agent producers to start collaborating on the use of genetic variation for the improvement of natural enemies.